Vibrio vulnificus RtxA1 Toxin Expression Upon Contact With Host Cells Is RpoS-Dependent - Guo, Rui Hong; Lim, Ju Young; Tra My, Duong Nu; Jo, Se Jin; Park, Jung Up; Rhee, Joon Haeng; Kim, Young Ran (Frontiers in Cellular and Infection Microbiology, 2018)
The expression of virulence genes in bacteria is known to be regulated by various environmental and host factors. Vibrio vulnificus, an estuarine bacterium, experiences a dramatic environmental change during its infection process. We reported that V. vulnificus RtxA1 toxin caused acute cell death only when close contact to host cells was allowed. A sigma factor RpoS is a very important regulator for the maximal survival of pathogens under stress conditions. Here, we studied the role of RpoS in V. vulnificus cytotoxicity and mouse lethality. The growth of rpoS mutant strain was comparable to that of wild-type in heart infusion (HI) media and DMEM with HeLa cell lysate. An rpoS mutation resulted in decreased cytotoxicity, which was restored by in trans complementation. Interestingly, host contact increased the expression and secretion of V. vulnificus RtxA1 toxin, which was decreased and delayed by the rpoS mutation. Transcription of the cytotoxic gene rtxA1 and its transporter rtxB1 was significantly increased after host factor contact, whereas the activity was decreased by the rpoS mutation. In contrast, the rpoS mutation showed no effect on the transcriptional activity of a cytolytic heamolysin gene (vvhA). Additionally, the LD50 of the rpoS mutant was 15-fold higher than that of the wild-type in specific pathogen-free CD-1 female mice. Taken together, these results show that RpoS regulates the expression of V. vulnificus RtxA1 toxin and its transporter upon host contact.